2010
DOI: 10.1348/135910709x437092
|View full text |Cite
|
Sign up to set email alerts
|

Temporal perspective and parental intention to accept the human papillomavirus vaccination for their daughter

Abstract: Human papillomavirus vaccination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Seven studies have quantitatively assessed parental acceptability of HPV vaccination in the UK and all suggest that around 74–88% of parents say they would accept HPV vaccination for their daughter (Brabin et al , 2006; Marlow et al , 2007b, 2008, 2009c; de Visser and McDonnell, 2008; Walsh et al , 2008; Morison et al , 2010). Findings in relation to ethnic minorities are limited and have been summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies have quantitatively assessed parental acceptability of HPV vaccination in the UK and all suggest that around 74–88% of parents say they would accept HPV vaccination for their daughter (Brabin et al , 2006; Marlow et al , 2007b, 2008, 2009c; de Visser and McDonnell, 2008; Walsh et al , 2008; Morison et al , 2010). Findings in relation to ethnic minorities are limited and have been summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that father’s roles in decision making are also important for finances or critical health events. Although several other studies have examined the preferences for the HPV vaccine among parents [19], [60], [66], [67], [68], [69] and among girls or young women [8], [47], [70], but none have compared parental preferences with adolescent preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Negative responses to information about the FOBt self‐sampling procedure might be particularly strong among individuals who have a general disposition to evaluate health behaviours according to their short‐ rather than long‐term consequences, a tendency which has been commonly referred to as being low in consideration of future consequences (CFC) 24 . People low in CFC have been found to be significantly less likely to engage in a variety of health behaviours including physical activity, diabetes screening, and HPV vaccine acceptance and more likely to engage in illness precipitating behaviours such as smoking 25–30 . Specifically, in the context of CRC screening, Orbell et al.…”
Section: Introductionmentioning
confidence: 99%